Application of Clustering Methods on Sexual Harassment Cases - Nurhafieza Nurhafieza; Novriyenni Novriyenni; Milli Alfhi Syari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Sexual harassment is one of the most common crimes in Indonesia, this act of sexual harassment can occur in daily life regardless of time, whether at work, on the street, or at home. Sexual abuse can come from unknown people, people who have hate, even people we care about. To solve problems that often occur in some cases including cases of sexual harassment that often occur in women based on certain factors, resulting in trauma to the victims who suffer physically, sexually, and psychologically, are required quick action to reduce the number in cases of sexual abuse in the area that often occur using clustering methods so that later it is expected to help the agency in socializing so that the community is more alert while in the place. From the testing conducted using 20 sexual harassment cases data there are 3 groups, namely group 1 there are 9 data and 2 groups there are 5 data and group 3 there are 6 data and it can be known that in cluster 1 is a group in the case data on sexual harassment based on the factors that are many causes with a total of 9 data and located in the age group (X) is 12-16 years, and for the group Sexual Harassment (Y) namely Physical Harassment and causing factor (Z) that is a lot due to individual factors.